Diagnostic tools used for melanoma: A survey of Australian general practitioners and dermatologists. (16th April 2021) - Nguyen, Jennifer; Ting, Sarajane; Paul, Eldho; Smith, Andrea L; Watts, Caroline G; Kelly, John; Cust, Anne E; Mar, Victoria
Abstract: Background/Objective: Diagnostic tools such as dermoscopy, sequential digital dermoscopy imaging (SDDI), total body photography (TBP) and automated diagnostic tools are available to assist in early melanoma diagnosis. The use, accessibility and barriers of dermoscopy have been well studied; however, there are few similar studies regarding SDDI, TBP and automated diagnostic tools. We aim to understand the use of these diagnostic aids amongst Australian general practitioners (GPs) and dermatologists. Methods: Between June 2019 and January 2020, GPs and dermatologists across Australia were invited to participate in an online survey. Surveys were distributed through GP and dermatology organisations. Results: A total of 227 survey responses were received, 175 from GPs and 52 from dermatologists. Amongst GPs, 44.6% worked in a skin cancer clinic. Dermoscopy was used at least occasionally by 98.9% of all GPs. SDDI was used by 93.6% of skin cancer GPs, 80.8% of dermatologists and 45.3% of generalist GPs. TBP was used or recommended by 77.1% of generalist GPs, 82.3% of skin cancer GPs and 86.5% of dermatologists. The most common barriers to the use of TBP were cost, limited accessibility, poor patient compliance, and time required for both patients and doctors. Very few clinicians reported using automated diagnostic tools. There was an interest in future diagnostic aids for melanoma in 88% of GPs and dermatologists. Conclusion: Dermoscopy, SDDI and TBP were commonly used by responding Australian skin cancer GPs and dermatologists in this survey. Automated diagnostic tools were not reported to be used routinely. Several barriers were identified for use of TBP.